Dynamic stability of gut microbiota in elite volleyball athletes: microbial adaptations during training, competition and recovery - Carlone, J.; Giampaoli, S.; Alladio, E.; Rosellini, G.; Barni, F.; Salata, E.; Parisi, A.; Fasano, A.; Tessitore, A. (Frontiers in Sports and Active Living, 2025)
Introduction: To examine how different weekly training and competition schedules influence gut microbiota composition in elite volleyball players, investigating the relationship between training and competition demands, recovery periods and microbial dynamics to identify potential biomarkers for training load and recovery status assessment.